Disorders of Thrombosis and Hemostasis in Pregnancy A Guide to Management - Cohen, Hannah.; Cohen, Hannah.; O'Brien, Patrick.; O'Brien, Patrick. (Springer London : Imprint: Springer, 2012)
Disorders of Thrombosis and Hemostasis In Pregnancy: A guide to management is a comprehensive guide to disorders of thrombosis and hemostasis in pregnancy. It highlights the latest developments and controversial issues, and the multidisciplinary approach provides authoritative clinical advice on state-of-the-art management. The disorders covered are highly pertinent to successful pregnancy outcome, and many may be associated with significant maternal and/or fetal morbidity, and even mortality. This book is relevant for individuals in all disciplines involved in the care of women with disorders of thrombosis and hemostasis in pregnancy.